Penerapan Asesmen Formatif Berbasis Quizizz untuk Meningkatkan Hasil Belajar Matematika Siswa SMA Negeri 2 Medan - Lase, Apricelly Gresya (Education Journal : Journal Educational Research and Development, 2024)
Mathematics education at SMA Negeri 2 Medan faces significant challenges due to the low learning outcomes of students, particularly in exponent material. This issue is influenced by students' low interest in mathematics, which is often perceived as difficult and unengaging. Teachers at the school also struggle to implement teaching methods that actively engage students in the learning process. These challenges highlight the need for innovation in teaching methods, such as implementing digital technology-based formative assessments. This study aims to analyze the effectiveness of using Quizizz-based formative assessment to improve the mathematics learning outcomes of class X.3 students on exponent material. The study employs Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests and observations and analyzed using gain scores to measure improvements between cycles. The results show that using Quizizz-based formative assessment significantly enhanced students' learning outcomes, with average scores increasing from 74.18 in Cycle I to 89.40 in Cycle II, and a gain score of 0.36 indicating moderate improvement. Additionally, the use of Quizizz improved student participation and motivation. Thus, Quizizz-based formative assessment is proven to be effective in enhancing mathematics learning outcomes and is recommended for application in other classrooms as an innovative teaching strategy.